Communities of practice: influences on pedagogical reasoning and action of nursing professors - do Carmo Menegaz, Jouhanna; Schubert Backes, Vânia Marli; Medina Moya, José Luis (Investigación y Educación en Enfermería, 2018)
Objective. To analyze how the practice shared in communities of teaching practice in public and private universities influences the pedagogical reasoning and action of nursing professors based on Wenger’s concepts of community, negotiation of meaning, and learning. Methods. Case study conducted with two professors teaching nursing in a public and a private university in Brazil. Data collection included triangulation of sources and was conducted from April 2014 to July 2015. Data were organized in ATLAS.ti and analyzed using the constant comparative method, which generated three meta-categories. Results. In both cases the program’s project is shared repertoire and grounds negotiation of meaning in the practice that takes place in the pedagogical reasoning and action phases but negotiation is different between communities and cases. Learning is either solitary or has the influence of at least one other member but does not occur on an institutional basis. Conclusion. Nursing schools could offer more than program’s project to the negotiation of meaning and improve learning on practice in their communities as police of teachers education to improve pedagogical reasoning. How to cite this article: Menegaz JC, Backes VMS, Medina JL. Communities of practice: influences on pedagogical reasoning and action of nursing professors. Invest. Educ. Enferm. 2018; 36(2):e02.